PROSPECT guideline for hallux valgus repair surgery: a systematic review and procedure‐specific postoperative pain management recommendations. Issue 9 (September 2020) - Korwin-Kochanowska, Katarzyna; Potié, Arnaud; El-Boghdadly, Kariem; Rawal, Narinder; Joshi, Girish; Albrecht, Eric; Joshi, G P; Pogatzki-Zahn, E; Van de Velde, M; Schug, S; Kehlet, H; Bonnet, F; et al.
Abstract : Hallux valgus repair is associated with moderate-to-severe postoperative pain. The aim of this systematic review was to assess the available literature and develop recommendations for optimal pain management after hallux valgus repair. A systematic review using PROcedure SPECific Postoperative Pain ManagemenT (PROSPECT) methodology was undertaken. Randomized controlled trials (RCTs) published in the English language from inception of database to December 2019 assessing postoperative pain using analgesic, anesthetic, and surgical interventions were identified from MEDLINE, EMBASE, and Cochrane Database, among others. Of the 836 RCTs identified, 55 RCTs and 1 systematic review met our inclusion criteria. Interventions that improved postoperative pain relief included paracetamol and non-steroidal anti-inflammatory drugs or cyclo-oxygenase-2 selective inhibitors, systemic steroids, ankle block, and local anesthetic wound infiltration. Insufficient evidence was found for the use of gabapentinoids or wound infiltration with extended release bupivacaine or dexamethasone. Conflicting evidence was found for percutaneous chevron osteotomy. No evidence was found for homeopathic preparation, continuous local anesthetic wound infusion, clonidine and fentanyl as sciatic perineural adjuncts, bioabsorbable magnesium screws, and plaster slippers. No studies of sciatic nerve block met the inclusion criteria for PROSPECT methodology due to a wider scope of included surgical procedures or the lack of a control (no block) group. The analgesic regimen for hallux valgus repair should include, in the absence of contraindication, paracetamol and a non-steroidal anti-inflammatory drug or cyclo-oxygenase-2 selective inhibitor administered preoperatively or intraoperatively and continued postoperatively, along with systemic steroids, and postoperative opioids for rescue analgesia.